Effect of warmed ropivacaine versus room temperature ropivacaine administered spinal anesthesia on recovery of lower limb muscle strength following total knee or hip replacement: a prospective, double-blind, randomized controlled study - Min Wang; Lu Meng; XiaoYuan Ma; Fan Li Bi; Jie Gao; Rongrong Wang; Jiawei Fan; Ye Liu; Longze Su; Lei Wang; Jun Zheng; Erfei Zhang (BMC Anesthesiology)
Abstract Background With the aging of the population, the number of hip and knee replacements worldwide continues to increase. Postoperative enhanced recovery has become a clinical focus, and an increasing number of hip and knee replacement surgeries are completed on an outpatient basis. Spinal anesthesia is the most widely used anesthetic method in clinical practice, but its disadvantages, such as slow recovery of lower limb muscle strength after operation, have hindered the rapid recovery of such patients. We found that the duration of lower limb motor block under spinal anesthesia with warmed ropivacaine was significantly shortened in clinical practice. We hypothesized that spinal anesthesia with warmed ropivacaine resulted in rapid recovery of lower limb muscle strength, improved limb mobility after hip/knee replacement surgery, increased ambulation from bed and reduced postoperative hospital stay. Methods Patients scheduled for hip or knee replacement surgery under spinal anesthesia were randomly assigned to normal temperature ropivacaine group (Group N: 1.0 ml of 1% ropivacaine with normal temperature 22.0–25.0 °C and 1.5 ml of cerebrospinal fluid are to be used for performing spinal anesthesia) and warmed ropivacaine group (Group W: 1.0 ml of 1% ropivacaine warmed to 36.0–37.0 °C and 1.5 ml of cerebrospinal fluid are to be used for performing spinal anesthesia). The incidence of patients achieving muscle strength grade 4 or higher in the operative limb within 3.5 h after anesthesia and the time to achieve grade 5 muscle strength, onset of sensory and motor block, duration of sensory block, intraoperative muscle relaxation score, the frequency of turning over in bed and the number of active functional exercises, the angles of knee joint flexion at 6 h and 24 h post-operation, first ambulation time, post-operative resting and motion pain score, the proportion of unilateral block, the time of first drinking and feeding, postoperative hospital stay and total hospital stay were record and analyzed. Results A total of 96 patients were recruited, 94 were randomized and 75 were finally analyzed, 38 in the Group N and 37 in Group W. The primary outcomes which were the proportion of patients with operative limb muscle strength not less than grade 4 at 3.5 h post-anesthesia was significantly increased 28.5% by warmed ropivacaine compared to room temperature ropivacaine and the time of operation limb achieving grade 5 muscle strength was significantly decreased in the Group W (3.7 [2.8, 5.0] hours) compared to the Group N (5.5 [3.7-7.0] hours). Secondary outcomes: The median active knee curvature on the operative side significantly increased by 17 degrees and 15 degrees, respectively, at 6 and 24 h after anesthesia. The onset time of sensory and motor nerve block were significantly decreased by warmed ropivacaine compared to room temperature ropivacaine. The unilateral block rate was significantly increased 36.2% by warmed ropivacaine compared to room temperature ropivacaine. Moreover, the median first walking time, post-operative hospital stay and the length of total hospital stay were significantly decreased 3 h, 3 days and 3 days, respectively. Although there are differences in the assessment of intraoperative muscle relaxation, the clinical significance is not obvious. Conclusions Warmed ropivacaine shortens the time for the recovery of lower limb muscle strength after spinal anesthesia, which is beneficial for the rapid recovery of patients undergoing lower limb joint replacement surgery and reduces the length of hospital stay. Trial registration Chinese Clinical Trial Registry ChiCTR2200057871 (registration date March 20, 2022).